Just opt in: How choosing to engage with technology impacts business students' academic performance. (March 2020) - Beatson, Nicola; Gabriel, Cle-Anne; Howell, Angela; Scott, Stephen; van der Meer, Jacques; Wood, Lincoln C.
Highlights: Behavioral engagement helps to explain academic success. Regardless of prior learning, behavioural engagement helps to predict success. More than just cognitive intelligence is needed when learning business subjects at university. Abstract: This study examines and compares the effect of gamification, in the form of a mobile application (app) 'Quitch', on the behavioral engagement and academic performance of business students in two first-year courses in accounting (n = 500) and management (n = 469). Both courses are compulsory; however, prior to the gamification intervention, student engagement was varied. The results indicate that 169 (33.58%) accounting and 135 (28.5%) management students actively used Quitch. The results show that behavioral engagement explains a large proportion of the variation around academic success, even when controlling for students' prior learning at high school. This study not only adds to the growing literature on gamification and engagement in business education, but also provides robust evidence for researchers arguing for more emphasis on the non-cognitive aspects of learning.